Estrabismo asociado a una alta miopía congénita en paciente masculino de 11 años. - Aguilar Zapater, Christoffer Kevyn (2022)
The clinical case presented exposes us about strabismus associated with high congenital myopia in an 11-year-old male patient, a deterioration that is due to ocular pathologies due to lack of control with the optometrist. The infant along with his parents suffer from myopia, but in the case of the minor, congenital high myopia was associated with strabismus, which generated the deviation of the left eye, a situation that affected his physical appearance, causing self-esteem problems and the advancement of nearsightedness interfering with daily and academic activities. The patient's parents mention that the child wears glasses since he was eight years old, but for financial reasons he has not been able to go to the clinic for a period of three years, a situation that caused the muscles of the left eye to atrophy, causing ocular deviation.